2011
DOI: 10.1073/pnas.1100300108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a covalent intermediate in DNA cleavage and rejoining by Escherichia coli DNA topoisomerase I

Abstract: DNA topoisomerases control DNA topology by breaking and rejoining DNA strands via covalent complexes with cleaved DNA substrate as catalytic intermediates. Here we report the structure of Escherichia coli topoisomerase I catalytic domain (residues 2-695) in covalent complex with a cleaved single-stranded oligonucleotide substrate, refined to 2.3-Å resolution. The enzyme-substrate intermediate formed after strand cleavage was captured due to the presence of the D111N mutation. This structure of the covalent top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 45 publications
5
93
0
Order By: Relevance
“…Recent work showed that three highly conserved arginine and aromatic residues in domain I (R169, R173, and Y177 in E. coli Top1) can account for DNA cleavage site selection of Top1, known as "−4C specificity," the fourth residue 3′ to the cleavage being a cytosine (23). These residues are absent in both eukaryotic and prokaryotic Top3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work showed that three highly conserved arginine and aromatic residues in domain I (R169, R173, and Y177 in E. coli Top1) can account for DNA cleavage site selection of Top1, known as "−4C specificity," the fourth residue 3′ to the cleavage being a cytosine (23). These residues are absent in both eukaryotic and prokaryotic Top3.…”
Section: Resultsmentioning
confidence: 99%
“…All type IA topoisomerases utilize an enzyme-bridged strand passage mechanism to change the topology of DNA and alter the linking number strictly in steps of one (6). In the crystal structures of type IA topoisomerase-DNA complexes, four conserved residues (Tyr, Lys, Arg, and Glu) form contacts at or near the scissile phosphate group (13)(14)(15). Roles for each amino acid have been proposed; Tyr is the nucleophile, Arg and Lys stabilize the penta-* This work was supported, in whole or in part, by National Institutes of Health Grant R01GM51350 (to A. M.).…”
mentioning
confidence: 99%
“…1 To whom correspondence should be addressed: Dept. valent protein-DNA complex, and Glu is the proton donor for the DNA cleavage reaction (13)(14)(15). A conserved nearby histidine plays a role in proton transfer, whereas three conserved acidic residues are involved in Mg 2ϩ binding (16 -20).…”
mentioning
confidence: 99%
“…The tyrosine residue of the active site covalently binds with the 5' phosphate, while the 3' end of the broken strand interacts with the enzyme noncovalently [10]. Magnesium ions, which are essential for catalysis, help to keep the 3' end of the cleaved strand in a proper position in the catalytic site [10,11]. After the complementary strand is passed through the resulting cleft to relax one supercoil, the enzyme cavity is closed, and the broken strand is ligated.…”
Section: Type Ia Dna Topoisomerasesmentioning
confidence: 99%